PTU-132 Autonomic Function Scores and Sleep Disturbance Scores in FGID Patients with and Without Upper Limb Temperature Dissociation. (17th August 2016) - Etherson, KJ; Emmett, C; Yiannakou, Y
Abstract : Introduction: Background Central autonomic dysfunction may result in a unilateral dissociation of temperature sensation, and is increasingly being investigated in FGIDs. The autonomic function score (AFS) and sleep disturbance score (SDS) are accepted measures in aiding the diagnosis of autonomic dysfunction. Aims: To assess and compare the AFS and SDS of consecutive FGID patients attending a specialist clinic, with and without upper limb temperature dissociation. Methods: Clinic attenders with a FGID diagnosis were sequentially invited to undertake the temperature sensation test. This comprised holding a bag of ice in both hands for 30 seconds and stating if they perceived the temperature to be either unilaterally colder or bilaterally equally cold. Unilaterally colder was considered to be evidence of upper limb temperature sensory dissociation. Patients had their total AFS calculated as follows: headaches, dizziness, sweating and sleep disturbance were severity scored using a Likert scale of 0–3, the sum of which is the AFS. The mean total AFS and mean sleep disturbance score were compared between patients with and without temperature dissociation. Results: 173 patients completed the AFS and 7 were excluded from the analysis for incomplete data leaving 166. 115 patients (69%) had upper limb temperature dissociation (group 1) compared to 51 (31%) with normal temperature sensation bilaterally (group 2). The mean total AFS in group 1 was 6.35 [SD 3.17] compared with 5.01 [SD 2.87] in group 2 [P = 0.009]. Mean sleep disturbance scores were not significantly different between the groups. Conclusion: FGID patients with upper limb temperature dissociation appear to have a significantly higher autonomic function score than those without temperature dissociation. This seems to suggest that the cause of the temperature dissociation may well be due to autonomic dysfunction acting at a central nervous system level. These results are an interesting observation from our clinic but are likely to be limited by inherent methodological biases in the data collection. Further investigation of autonomic function scores and temperature dissociation are required in formal and appropriately powered clinical research studies to validate these findings. Disclosure of Interest: None Declared